PERBAIKAN SALURAN SUNGAI DI CIHIDEUNG UDIK KAMPUNG PASAR REBO - Syaiful Syaiful; Muhammad Nasrudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
In river channel embankment repair activities, an important thing to consider is the availability of land. The flow of the Cihideung Udik River Channel in Pasar Rebo Village Some of the canal bodies have been damaged, especially on the embankment of the river channel. The channel belongs to Bogor Regency, which irrigates from upstream to downstream, its surface water source from the Cihud Cihideung Udik Dam. The original open channel network from the Cihud Dam which connects the Cinangneng River and the Cihideung Udik River in Ciampea District, the embankment on the river channel from the left embankment with a length of one meter has been damaged, due to heavy water flowing in the rainy season. Damage to embankments in river channels, the results obtained. Dimensions of the river channel are trapezoidal in shape, namely: the bottom width of the channel is 1,40 m, the top width of the channel is 1,65 m, and the height is 0.90 m.